The quality of life of Croatian women after mastectomy: a cross-sectional single-center study - Stana Pačarić; Jozo Kristek; Jure Mirat; Goran Kondža; Tajana Turk; Nikolina Farčić; Želimir Orkić; Ana Nemčić (BMC, 2018)
Abstract Background Measuring the quality of life (QoL) of women with breast cancer is an important aspect of measuring treatment success. In Croatia, no QoL studies have been carried out with a focus on patients after mastectomy. The aim of this study was to examine QoL 1 month and 1 year after mastectomy. Methods This cross-sectional single-center study of quality of life was conducted in 101 patients, 50 of whom had undergone a mastectomy 1 month prior, and 51 of whom had undergone a mastectomy 1 year prior. The study was conducted from July 2015 to June 2016. The questionnaires used in the study were developed by the European Organisation for Research and Treatment of Cancer (EORTC). The questionnaire EORTC QLQ-C30 assesses the QoL of cancer patients, and the questionnaire EORTC QLQ-BR23 is a disease-specific breast cancer module. A chi square test, Fisher's exact test, Kolmogorov-Smirnov test, Student's t-test and Mann-Whitney U test were performed in the statistical analysis using the statistical program SPSS (Inc. Released 2008. SPSS Statistics for Windows, Version 17.0. Chicago: SPSS Inc.). Results Patients who had undergone a mastectomy a year earlier placed a higher value on their health state than did those who had undergone a mastectomy a month earlier. The most affected values of functional status on the EORTC QLQ-C30 scale were emotional functioning (37.5 [95% CI 33.3-61.6]) and sexual functioning (16.67 [95% CI 0-33.3]) 1 month and 1 year after mastectomy, respectively. The most affected symptoms on the EORTC QLQ-C30 scale were hair loss 66.67 [95% CI 33.3-100]) and fatigue 33.33 [95% CI 24-44]) 1 month and 1 year after mastectomy, respectively. Conclusion In our study, both functional and symptom scales were more affected in women 1 month after mastectomy. QoL was considerably improved in women 1 year after the surgery compared to 1 month after mastectomy. The results of this study could contribute to the public awareness of the QoL of breast cancer patients.